2015
DOI: 10.1002/hed.23947
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity and performance status as independent prognostic factors in patients with head and neck squamous cell carcinoma

Abstract: Background The purpose of this study was to evaluate the individual and combined relationship of comorbidity and performance status (PS) on head and neck squamous cell carcinoma (HNSCC) survival. Methods Six hundred patients with HNSCC were prospectively recruited. Comorbidity and PS were measured using the Charlson Comorbidity Index (CCI) and the Eastern Cooperative Oncology Group (ECOG) Scale. Outcomes were overall survival (OS) and cancer‐specific survival (CSS). Results A total of 48.3% of the patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 25 publications
4
48
1
Order By: Relevance
“…The head and neck oncology population has been assessed with other indices, including the Kaplan‐Feinstein score comorbidity index, CCI, and Adult Comorbidity Evaluation‐27 demonstrating decreased survival rates and increased complications with increasing index scores. We found when comparing the modified frailty index score to the CCI directly, only the modified frailty index score was associated with increasing Clavien‐Dindo classification IV complication rates in patients who underwent flap reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…The head and neck oncology population has been assessed with other indices, including the Kaplan‐Feinstein score comorbidity index, CCI, and Adult Comorbidity Evaluation‐27 demonstrating decreased survival rates and increased complications with increasing index scores. We found when comparing the modified frailty index score to the CCI directly, only the modified frailty index score was associated with increasing Clavien‐Dindo classification IV complication rates in patients who underwent flap reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…Higher comorbidity scores have been shown to be adversely associated with overall survival (OS), choice of treatment modality, and treatment outcomes in head and neck cancer . People with head and neck cancer tend to have a higher comorbidity burden compared to the general population . This may partially be attributable to their engagement in adverse health behaviors such as smoking and high alcohol intake that increase the risk of the development of comorbid conditions as well as head and neck cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have examined the impact of comorbidities on outcomes in head and neck cancer . However, no prospective study has been able to adjust for HPV status, behavioral, and social variables in their study populations while stratifying for head and neck cancer subsite in the same model.…”
Section: Introductionmentioning
confidence: 99%
“…However, a limitation of the CDS in patient registries is that it is often a reflection of the number of comorbidities and not necessarily the severity of the comorbidities. Similarly, there is no information in the NCDB on each patient's performance status or smoking history, both of which are important prognostic factors for patients with HNSCC . Recent single‐institution data have demonstrated that elderly patients with HNSCC receiving definitive CRT or RT alone received less toxic concurrent chemotherapy but experienced higher rates of hospitalization, lower rates of feeding gastrostomy tube removal, and a higher rate of death within 3 months of treatment initiation .…”
Section: Discussionmentioning
confidence: 99%